(untitled) (ResearchJet Journal of Analysis and Inventions, 2023)
Objective: to study the role of endothelial dysfunction in combined and multiple injuries of long bones and ways of its correction. Material and methods. The objects of clinical study were 48 patients with polytrauma admitted to the department of emergency traumatology of the Multidisciplinary Clinic of the Tashkent Medical Academy.Results: In patients with polytrauma in the acute period, there is an increase in the serum content of endothelin-1 and a decrease in the level of nitric oxide metabolites. Their severity corresponds to the severity of the injury and the patient’s condition. The favorable course of polytrauma is characterized by a moderate decrease in the level of endothelin-1 and an increase in nitric oxide metabolites in the dynamics of traumatic disease, especially when the immunocorrector polyoxidonium is prescribed.Conclusion: in polytrauma, endothelial dysfunction reflects the adaptive reactions of the body, allows you to determine the severity of the injury and predict the outcome.